The effects of intralingual and interlingual contrast and comparison on learning english relative clauses among EFL Chinese learners - Chaohai, Lin (2023)
Intralingual and interlingual contrast and comparison is an effective teaching method for language learning. This study investigates the effects of intralingual and interlingual contrast and comparison on the learning of English relative clauses for Chinese Senior high school students. The study utilized a quasi-experimental research design involving 106 students, where the experimental group received the new teaching method of intralingual and interlingual contrast and comparison. To investigate the effect of the new teaching method and explore students’ views on learning English relative clauses thoroughly, both quantitative and qualitative research methods were utilized. The data was collected via experimental research (n=106) and focus group interviews (n=6). Research findings suggested that applying intralingual and interlingual contrast and comparison could be considered as an effective teaching method in improving students’ performance in learning English relative clauses, highlighting the effectiveness of the new teaching method on learning English relative clauses. The findings also revealed students’ challenges in learning English relative clauses, namely difficulties in rules memorization, confusion with the relative adverbs and prepositions+ relative pronoun which. And students considered that the new teaching method was simple and easy to understand in learning English relative clauses. In addition, the study provides a new perspective for other areas or countries on the learning of ERCs since there are a lot of similarities between personal pronouns and relative pronouns, between the prepositional phrases and relative adverbs in English itself and between English relative clauses and relative clauses in other languages. Finally, the study provided valuable insights for instructors on teaching English relative clauses, as well as providing suggestions for the Cognitive code approach and Contrastive analysis